Wrath of the triple goddess eaudiobook - Riordan, Rick (Percy Jackson and the Olympians, 2024)
In his continuing quest to earn college recommendation letters from the gods, Percy has to pet sit the goddess Hecate's polecat and giant mastiff during Halloween week. What could go wrong? Rick Riordan's newest Percy Jackson adventure is full of hilarious set pieces, a diverse cast of gods and monsters, and many other delightful tricks and treats. Percy Jackson, now a high school senior, needs three recommendation letters from the Greek gods in order to get into New Rome University. He earned his first one by retrieving Ganymede's chalice. Now the goddess Hecate has offered Percy another "opportunity"—all he has to do is pet sit her polecat, Gale, and mastiff, Hecuba, over Halloween week while she is away. Piece of cake, right? Percy, Annabeth, and Grover settle into Hecate's seemingly endless mansion and start getting acquainted with the fussy, terrifying animals. The trio has been warned not to touch anything, but while Percy and Annabeth are out at school, Grover can't resist drinking a strawberry-flavored potion in the laboratory. It turns him into a giant frenzied goat, and after he rampages through the house, damaging everything in sight, and passes out, Gale and Hecuba escape. Now the friends have to find Hecate's pets and somehow restore the house, all before Hecate gets back on Saturday. It's going to take luck, demigod wiles, and some old and new friends to hunt down the animals and set things right again.